Empirical analysis of innovation and productivity in services firms: The case of South Africa. Issue 1 (2nd January 2023) - Kasongo, Atoko; Sithole, Moses; Buchana, Yasser
Abstract : The purpose of this paper is to investigate the impact of innovation on productivity in the services sector firms in South Africa. Using a three-stage econometric model we find that service sector firms are innovative. We show that firm size, public financial support, patent protection and market sources of information have a positive impact on the decision to innovate. The level of investment in innovation significantly influences the success of both technological and non-technological innovations in service sector firms. The results find that both technological and non-technological innovations have a positive impact on labour productivity, with a greater impact from non-technological innovation.